2013
DOI: 10.1093/jac/dks531
|View full text |Cite
|
Sign up to set email alerts
|

Tn6198, a novel transposon containing the trimethoprim resistance gene dfrG embedded into a Tn916 element in Listeria monocytogenes

Abstract: This study reports the first Tn916-like element associated with a trimethoprim resistance gene, as well as the first fully characterized transposon conferring multidrug resistance in L. monocytogenes. This is of concern, as trimethoprim is administered to listeriosis patients with β-lactam allergy and as Tn6198 has a large potential for dissemination, indicated by both intra-species and inter-genus transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…This gene encodes an anti-restriction protein that is probably not part of the typical MPF FA (68). The last gene of the operon, orf24 Tn916 , is often found in other MPF FA systems isolated from the rest of the operon (69), or even not mentioned as part of the conjugative machinery (70). It is thus probably not an essential component of MPF FA .…”
Section: Resultsmentioning
confidence: 99%
“…This gene encodes an anti-restriction protein that is probably not part of the typical MPF FA (68). The last gene of the operon, orf24 Tn916 , is often found in other MPF FA systems isolated from the rest of the operon (69), or even not mentioned as part of the conjugative machinery (70). It is thus probably not an essential component of MPF FA .…”
Section: Resultsmentioning
confidence: 99%
“…The overall G+C content of Tn 6188 (32.9%), being considerably lower than the overall G+C content of Listeria genomes, suggests a relatively recent transfer of Tn 6188 into L. monocytogenes . In line with this, to our knowledge, only few transposons have been identified in L. monocytogenes so far: Tn 5422 , which is found on the majority of Listeria plasmids, conferring tolerance to cadmium [44-46], the IS 1216 composite transposon harboring the bcrABC resistance cassette [20], Tn 6198 , a conjugative Tn 916 -like transposon conferring resistance to antibiotics [47], a Tn 554 -like transposon putatively involved in arsenic resistance [48], and an integrative conjugative element belonging to the Tn 916 family which has been found in the L. monocytogenes EGDe genome [49]. In contrast to Tn 6188 , Tn 5422 and Tn 6198 have a G+C content of 37.9%, which is much more similar to the overall G+C content of L. monocytogenes genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Other parts of the Tn916 transposon bore genetic elements for bacterial conjugation. Although a circular form of the 3.3-kb sequence was detected in L. monocytogenes, the dfrG-containing fragment could not be transferred on its own to L. monocytogenes or to Enterococcus faecalis (30). Transfer of the dfrG gene was observed only when it was part of Tn916, which provided genetic elements that were required for conjugation.…”
Section: Discussionmentioning
confidence: 95%
“…The element was integrated into a sequence that was homologous to SPy_1769. Recently, Bertsch et al (30) identified an identical 3.3-kb sequence, which was a part of the transposon Tn916 in Listeria monocytogenes. Other parts of the Tn916 transposon bore genetic elements for bacterial conjugation.…”
Section: Discussionmentioning
confidence: 99%